Remarks to the Heads of State of the Central African Economic and Monetary Community - Malpass, David (World Bank, Washington, DC, 2021)
Bank Group President David Malpass said that deep structural reforms are needed now more than ever to secure social cohesion and put the region on a sustainable and more inclusive development path. The World Bank Group has maintained a long-standing partnership with Central African Economic and Monetary Community (CEMAC) and its individual members, providing a range of support including investment programs, budget support, advisory services, and technical assistance. The World Bank is partnering with the African Union to support the Africa Vaccine Acquisition Trust (AVAT) with resources to purchase and deploy single-dose vaccines for up to four hundred million people across Africa. Debt transparency and sustainability will be vital to a sustained recovery and attracting new investment. He spoke about two critical paths to help strengthen implementation of reforms and policies going forward. He concluded by saying that this day's summit and its strong political endorsement for the next phase of regional structural reforms is thus critical for the emergence of a more sustainable and more inclusive growth path for CEMAC in the future.